Histone deacetylases 1 and 2 restrain CD4+ cytotoxic T lymphocyte differentiation - Teresa Preglej; Patricia Hamminger; Maik Luu; Tanja Bulat; Liisa Andersen; Lisa Göschl; Valentina Stolz; Ramona Rica; Lisa Sandner; Darina Waltenberger; Roland Tschismarov; Thomas Faux; et al. (JCI Insight, 2020)
Some effector CD4+ T cell subsets display cytotoxic activity, thus breaking the functional dichotomy of CD4+ helper and CD8+ cytotoxic T lymphocytes. However, molecular mechanisms regulating CD4+ cytotoxic T lymphocyte (CD4+ CTL) differentiation are poorly understood. Here we show that levels of histone deacetylases 1 and 2 (HDAC1-HDAC2) are key determinants of CD4+ CTL differentiation. Deletions of both Hdac1 and 1 Hdac2 alleles (HDAC1cKO-HDAC2HET) in CD4+ T cells induced a T helper cytotoxic program that was controlled by IFN-γ–JAK1/2–STAT1 signaling. In vitro, activated HDAC1cKO-HDAC2HET CD4+ T cells acquired cytolytic activity and displayed enrichment of gene signatures characteristic of effector CD8+ T cells and human CD4+ CTLs. In vivo, murine cytomegalovirus–infected HDAC1cKO-HDAC2HET mice displayed a stronger induction of CD4+ CTL features compared with infected WT mice. Finally, murine and human CD4+ T cells treated with short-chain fatty acids, which are commensal-produced metabolites acting as HDAC inhibitors, upregulated CTL genes. Our data demonstrate that HDAC1-HDAC2 restrain CD4+ CTL differentiation. Thus, HDAC1-HDAC2 might be targets for the therapeutic induction of CD4+ CTLs.